OPTIMALISASI UMKM DALAM PEMANFAATAN TEKNOLOGI DIGITAL DI MASA PANDEMI COVID-19 DI LINGKUNGAN KECAMATAN CIBITUNG, KABUPATEN BEKASI - Fadhilah, Nur Ahmad; Putra, Purnama; Rahmawati, Rafika; Basri, Hasan (DEVOSI, 2021)
The Covid-19 pandemic that occurred in Indonesia required MSME entrepreneurs (Micro, Small and Medium Enterprises) to find ideas to market their products. So with this problem, it can be concluded that digital technology during the pandemic is very much needed to encourage the promotion of MSME products. The implementation method used is in the form of counseling and training on technology to promote MSME products. The results of this activity show an increase in knowledge of their awareness of using digital technology, a total of 5 entrepreneurs who have been socialized all already understand the use of digital technology and even all of them have practiced it themselves. By making product posts, making posts related to merchandise, making income reports or expenditure. As well as buying through E-commerce that has been taught.